211k views
0 votes
HELP!!!!

this is very important and the deadlines at 11:59 PLEASE HELP YOU CAN!!!!​

HELP!!!! this is very important and the deadlines at 11:59 PLEASE HELP YOU CAN!!!!​-example-1
User Rberggreen
by
5.7k points

2 Answers

1 vote

X is equal to 1 my friend

User Nitrodon
by
6.3k points
3 votes

Answer:

It's literally just

x=0 or x=1

step by step:

Multiply all terms by (x-2)(x+1) and cancel:

x(x+1)+(x−1)(x−2)=−1(x−2)(x+1)

2x2−2x+2=−x2+x+2(Simplify both sides of the equation)

2x2−2x+2−(−x2+x+2)=−x2+x+2−(−x2+x+2)(Subtract -x^2+x+2 from both sides)

3x2−3x=0

3x(x−1)=0(Factor left side of equation)

3x=0 or x−1=0(Set factors equal to 0)

x=0 or x=1

Check answers. (Plug them in to make sure they work.)

x=0(Works in original equation)

x=1(Works in original equation)

User MarsOne
by
5.9k points